2018
DOI: 10.1016/j.jgar.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Rezafungin (CD101), a next-generation echinocandin: A systematic literature review and assessment of possible place in therapy

Abstract: Rezafungin is a novel echinocandin currently in phase 2 studies, differentiated by a long half-life that allows once-weekly dosing and a safety profile that allows higher doses. Several potential areas of use for rezafungin were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 25 publications
1
51
0
1
Order By: Relevance
“…Echinocandins have some important limitations, despite their proven safety and efficacy (9,15). Most notably, the daily parenteral dosing requirement complicates administration postdischarge in patients requiring extended therapy.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Echinocandins have some important limitations, despite their proven safety and efficacy (9,15). Most notably, the daily parenteral dosing requirement complicates administration postdischarge in patients requiring extended therapy.…”
mentioning
confidence: 99%
“…Although step-down therapy from an echinocandin to fluconazole may partially address the outpatient antifungal expenditure, it is complicated by the increasing rates of resistance to fluconazole among common species of Candida (1,7,9,14,16). Other potential drawbacks of the available echinocandins for clinical application are the use of a fixed dose irrespective of body size or species susceptibility (S) and emerging resistance mediated by mutations in the fks genes (15,17). It has been suggested that underdosing of echinocandins, coupled with poor penetration to certain body sites, may partially account for the emerging echinocandin resistance (15,18,19).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Rezafungin (CD101) is a new echinocandin antifungal agent in development to treat candidemia and invasive candidiasis and to prevent invasive fungal diseases caused by Candida , Aspergillus , and Pneumocystis spp among immunosuppressed patients, including those undergoing allogeneic blood and marrow transplantation and those receiving cytotoxic chemotherapy for hematologic malignancies . Echinocandins inhibit the synthesis of 1,3‐β‐D‐glucan, an essential component of the fungal cell wall, resulting in cell wall stress and death .…”
mentioning
confidence: 99%